Hubungan Asupan Zat Gizi Dengan Tingkat Kebugaran Usia Lanjut Kelompok Binaan Puskemas di Kecamatan Kota Arga Makmur Kabupaten Bengkulu Utara = The Relationship between Nutrition Intake and Elderly Physical Fitness of... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstrack Naturally old people are undergoing physical, biological, mental and social decline and having much illness. Doing physical exercise can bring positive effect to elderly physical capability if it is done properly and correctly. However, doing physical exercise needs nutrition intake gained from daily food with sufficient nutrition as recommended in order to stay fit and healthy. The aims at the study was to know the relationship between nutrition intake and physical fitness of elderly nurture group. The study was an exploratory type which used cross sectional design with quantitative approach. Population consisted of the elderly aging 60-70 years at subdistrict of Arga Makmur City. The subject comprised group of old people doing physical exercise at 11 integrated service center for the elderly. There were 62 people Tandomly selected. Independent variables included nutrition intake, nutritional status, eating habit and elderly characteristics, whereas dependent variable included physical fitness. Data were analyzed using chi-square and double logistic regression. Average of eldrely nutrition intake against nutrition sufficiency index was 56.5% with more or less 8.1 for energy, 72.2% with more or less 25,1 for protein, 56.8 % with more or less 20.8 for fat, 99.9% with more or less 33.2 for carbohydrate, 9.3% for B, vitamin, 11.2% for B12 vitamin, 10.5% for B6 vitamin, 10.4% for E vitamin, 13.5% for C vitamin,48.7% for A vitamin, 5.8% for folat acid, 9.3% for calcium, 9.6% for iron and 6.2% for zink. Nutritional status based on mass body index showed as much as 46.8% was nutrition deficient and 30.6% was nutrition sufficient, whereas 59.7% had improper eating habit. As much as 69.4% had low physical fitness (p>0.05), but there